(3Yde GdELJeGY GdQjaj GdeYGUQ hGdEJLGgGJ GdMOjKI aj OQGSGJ GdJfejI GdQjajI (B/s - (3YHO GdbGOQ, eMeO YdGA GdOjfs ((3GdEScfOQjI(B: s (3efTCI GdeYGQa(B, s, 2003)
(3GdJfejI hGdJMOjK,GdefGgL GdeNJdaI dJfejI GdeLJeYGJ GdQjajI,efGgL JfejI GdeLJeYGJ GdQjajI GdeMdjI,GdefGgL GdJfehjI GdHOjdI,GdJcGed Hjf hLgGJ GdfXQ GdeNJdaI Mhd GdefGgL GdJfehjI,CUhd GdHMK GdYdej hefGgLg,GdEJLGgGJ GdMOjKI aj efGgL hWQb HMhK GdOQGSGJ GdGLJeGYjI,GdGSJTYGQ Yf HYO hfXe GdeYdheGJ GdLZQGajI,CeKdI JWHjbjI aj OQGSGJ Yde GdGLJeGY GdQjaj GdeYGUQ ddEJLGgGJ GdMOjKI aj OQGSGJ GdJfejI GdQjajI hefGgL GdHMhK GdeSJNOeI,YQV fehPL HMKj ebJQM deTQhY bhej fMh HfGA bGYOI eYdheGJ dHQGeL GdJfejI GdQjajI hGdRQGYjI GdeSJOGeI HefWbI GdSGMd GdTeGdj GdZQHj hhGMI SjhI HESJNOGe GdESJTYGQ Yf HYO hfXe GdeYdheGJ GdLZQGajIs
(3HjHdjhZQGajG (B:(3U(B.325s
Keywords: (3GdJfejI GdQjajIs; (3OQGSGJ MOjKIs; (3Yde GdGLJeGYs